ASPEK BERPIKIR KRITIS DALAM BUKU TEKS BAHASA INDONESIA KELAS VII PENERAPAN KURIKULUM MERDEKA - Sulfia Arianti; Sakaria Sakaria; Hasriani Hasriani (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the aspects of critical thinking contained in Indonesian language textbooks for Grade VII. This type of research is qualitative research. The focus of this research is the aspects of critical thinking, namely basic clarification, providing reasons for a decision, inferring, further clarification, conjecture and integration. The data source in this study is the Indonesian language textbook for class VII, first printing 2021 with a thickness of 220 pages. Data collection techniques are reading, quoting and documentation techniques. Data analysis techniques were carried out by data reduction, data presentation, and conclusion drawing/verification. The results showed that the grade VII Indonesian textbooks included aspects of basic clarification, giving reasons for a decision, concluding, further clarification, conjecture and integration.